The Impact of Neoliberal Policies on Social Welfare: Case Studies in Developing Countries - Rosari, Dina; Fatchur Rohman; Latuheru, Anita; Pasalbessy, Victor F. (Nomico, 2024)
This article analyzes the impact of neoliberal policies on social welfare in developing countries, focusing on the implementation of free market principles, privatization, deregulation, and a reduced role of the state in the economy. While these policies aim to improve economic efficiency and growth, this research finds that neoliberal implementation in developing countries often exacerbates social inequality and reduces the poor's access to basic services such as health, education and social protection. The research identifies negative impacts such as public sector privatization that increases costs for low-income earners, deregulation that makes workers more vulnerable to exploitation, and social budget cuts that reduce the quality of services for marginalized groups. Although some countries experienced economic growth as a result of these policies, the unequal distribution of economic benefits led to increased social inequality. This article suggests the need for more inclusive and sustainable economic policies that can mitigate the negative impacts of neoliberalism, as well as strengthen social security and access to basic services in developing countries.